BEHAVIOR OF PHYSICAL AND DENSITY PROPERTIES OF SOFT SOIL STABILIZED WITH NICKEL SLAG - Gaus, Abdul; Rauf, Ichsan; Arya Utama, Komang; YS, M. Taufiq; Linda (International Journal of Research -GRANTHAALAYAH, 2024)
Soft soils have become a significant challenge in geotechnical engineering, due to their low bearing capacity and susceptibility to deformation. Chemical stabilization using nickel slag is an alternative solution and is considered more environmentally friendly. This article focuses on the utilization of nickel slag as a binder material aimed at behavior of physical and mechanical properties of soft soil stabilized with nickel slag soft soil. The nickel slag was carried out with variations of 3%, 6%, 9% and 12% by weight of soil. All the test using ASTM procedure in order to gain physical and mechanical value. The results of this study showed that plasticity index decrease with the increasing of slag nickel concentration, where it is an indication of a change in soil consistency, shifting from initially soft to now medium. Futher, the optimum dry density (d-opt) value of the original soil used was 1.09 gr/cm3, while the optimum dry density (d) values at 3%, 6%, 9% and 12% nickel slag addition were 1.12 gr/cm3; 1.15 gr/cm3; 1.19 gr/cm3 and 1.22 gr/cm3, respectively. These results show that the presence of nickel slag can increase influence the physical and density properties of soft soil, which indicates that nickel slag has the potential to be used as a stabilization material in soft soil.